Radiographic Evaluation of the Thoracic Limb Hooves of Draft Horses in Chirripó National Park - Batalla-Zeledón, Ramón (2025)
At Chirripó National Park (Costa Rica), workhorses are used to transport materials and luggage to the Base Crestones lodge, situated 8.6 miles from the park entrance. SENASA, CREW, and CRC Chirripó have conducted periodic welfare inspections, which have revealed that one of the primary issues is the condition of the horses’ hooves. The objective of this study is to evaluate the condition of the hooves of the pack horses working in the Chirripó National Park by using radiological diagnosis. Radiographic measurements of the forelimbs of 30 horses were analyzed using Metron Hoof® software and evaluated using descriptive statistical analysis. The hoof angle obtained was 47.82° ± 2.60°, and the angles of the proximal and distal interphalangeal joints were 3.75° ± 3.26° and 8.32° ± 5.54°, respectively. The latter confirmed the diagnosis, with 100% of the animals studied presenting a broken-back hoof-pastern axis. It is recommended to implement measures that correct these conditions to improve the quality of life for the horses.